PENGARUH PENDIDIKAN KESEHATAN MENGGUNAKAN MEDIA LEAFLET TERHADAP TINGKAT PENGETAHUAN TENTANG SEKSUAL PRANIKAH PADA KESEHATAN REPRODUKSI REMAJA DI SMA PARULIAN 2 MEDAN - Harianja, Laura; Simanullang, Rostime Hermayerni (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Background: Health education plays a crucial role in raising adolescents' awareness of reproductive health. Adolescents are vulnerable to premarital sexual behavior, which poses risks such as unintended pregnancies and sexually transmitted infections. Objective: To examine the effectiveness of leaflet media in improving the knowledge of high school students at SMA Parulian 2 Medan regarding the impacts of premarital sexual behavior. Method: This study employed a pre-experimental design using the One Group Pre-Test – Post-Test method. The research sample consisted of 69 twelfth-grade students selected through total sampling. Data were collected through questionnaires and analyzed using the Wilcoxon Signed Ranks Test. Results: The study showed a significant increase in students' knowledge levels after receiving education through leaflets (p = 0.000). Before the intervention, 79.7% of students had low knowledge, whereas after the intervention, 76.8% of students reached the good knowledge category. Conclusion: Leaflet media is effective in enhancing adolescents' understanding of reproductive health, thereby assisting them in making more informed decisions.